Komunikasi Penerimaan Aktif Generasi Muda Muslim Terhadap Pengajian Media Sosial Ustadz Populer Tema Toleransi dan Moderasi Beragama - Sunaryanto (INSTITUT PEMBINA ROHANI ISLAM JAKARTA, 2026)
The aim of this research is to analyze the communication of active acceptance by the younger generation of Muslims regarding religious tolerance and moderation preached by popular religious teachers through social media studies. The research method used is qualitative with an active acceptance communication theory approach developed by Andi Faisal Bakti. The conclusion of this research is that Muslim youth interpret religious tolerance and moderation to strengthen their respective ideologies. This young generation of Muslims accepts and interprets religious messages and tolerance in accordance with their social and educational background so that their meaning becomes plural. The younger generation of conservative Muslims wants tolerance not to violate the boundaries of the faith or conflict with the text of the Qur’an and hadith. On the other hand, this young Muslim generation is moderate in accepting and maintaining social and muamalah relations. The younger generation of Muslims who memorize the Koran actively filters the persuasion of social media preaching through a framework of faith (faith) and ideological immunity (antibody) in order to balance moral solutions (panacea) with classical literature. Through a process of negotiation and rejection of indoctrination, they construct the meaning of moderation as a commitment to peace (bullet) which still maintains the limits of the faith from the extreme effects of boomerang.